Linguistic and Linguapoietic Characteristics of the Concept - Sattorova Nafisa Isomidinovna (Genius Journals, 2023)
This article provides information about the linguistic and linguapoetic features of the term "concept". The article also describes the views of world and Uzbek linguists about the concept.
Keywords: cognitive; anthropocentric; linguoculturology; perception